2003
DOI: 10.1091/mbc.e02-08-0548
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Bullous Pemphigoid Antigen 1 (BP230) and Desmoplakin with Intermediate Filaments Is Mediated by Distinct Sequences within Their COOH Terminus

Abstract: The bullous pemphigoid antigen 1 (BP230) and desmoplakin (DP) are members of the plakin protein family of cytolinkers. Despite their homology, their COOH termini selectively bind distinct intermediate filaments (IFs). We studied sequences within their COOH termini required for their interaction with the epidermal keratins K5/K14, the simple epithelial keratins K8/K18, and type III IF vimentin by yeast three-hybrid, cell transfection, and overlay assays. The results indicate that BP230 interacts with K5/K14 but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
131
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(142 citation statements)
references
References 56 publications
10
131
0
1
Order By: Relevance
“…Furthermore, the linker and the B domain might have different roles in the binding to IFs. It was reported that the linker, B and C subdomains of desmoplakin and BP230 play an important role in the specificity and interaction with IFs (Fontao et al, 2003). We observed preferential binding of epiplakin fragments to different type of keratins.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Furthermore, the linker and the B domain might have different roles in the binding to IFs. It was reported that the linker, B and C subdomains of desmoplakin and BP230 play an important role in the specificity and interaction with IFs (Fontao et al, 2003). We observed preferential binding of epiplakin fragments to different type of keratins.…”
Section: Discussionsupporting
confidence: 48%
“…Expression, purification of keratins, filaments assembly and dot blot overlay assays The expression and purification of human keratins were the same as described by Fontao et al (Fontao et al, 2003) except that the proteins were extracted from final pellets by urea buffer (25 mM Tris-HCl, pH 8.0, 500 mM NaCl, 5 mM imidazole, 8 M urea). After an additional centrifugation at 37,500 g, the supernatants were collected and the urea concentration was adjusted to 6 M. Keratins were further purified using a 5 ml Hi-Trap Ni-NTA column (Pharmacia) and eluted by a gradient of 5-500 mM imidazole.…”
Section: Epiplakin Antibodymentioning
confidence: 99%
“…Keratins interact with the plectin and DSP carboxy termini through segments of their rod domain (Meng et al 1997;Fontao et al 2003;Bouameur et al 2014). Association with keratins is regulated by serine phosphorylation and arginine methylation of the DSP tail, involving a coordinated activity of glycogen synthase kinase 3 (GSK3) and protein arginine methyltransferase 1 (PRMT1).…”
Section: Interdependence Of Keratins and Desmosomesmentioning
confidence: 99%
“…In addition, BPAG1e also binds to the epidermal cytokeratin network that is formed by keratins 5 and 14 (K5, K14) in basal keratinocytes and thereby connects them to the extracellular matrix (Fontao et al, 2003;Guo et al, 1995). In the epidermis, loss of BPAG1e leads to a selective fragility of the base of the columnar basal cells, resulting in blisters and compromised wound healing (Guo et al, 1995).…”
Section: Cellular Functions Of Bpag1mentioning
confidence: 99%